2000
DOI: 10.1590/s0102-311x2000000200006
|View full text |Cite
|
Sign up to set email alerts
|

O uso prolongado de benzodiazepínicos em mulheres de um centro de convivência para idosos

Abstract: While experts recommend caution against long-term benzodiazepine use in the elderly, survey data suggests that the use of benzodiazepine increase with age. The patterns of benzodiazepine use and factors associated with long-term use in population at risk were studied with a standarlized questionnaire applied to 634 women over 60, who attended a daycare center for older people in Rio de Janeiro between May, 1992 and December, 1995. Prevalence of benzodiazepine use in the last 15 days was 21.3% (CI 95% 18.1-24.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
1
35

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 34 publications
4
11
1
35
Order By: Relevance
“…In the study population predominated the use of benzodiazepine with therapeutic anxiolytic action, as well the use of long half-life medications. The predominance of Bromazepam use was paralleled by another Brazilian study, 13 but is not consistent with that observed in developed countries.…”
contrasting
confidence: 75%
See 2 more Smart Citations
“…In the study population predominated the use of benzodiazepine with therapeutic anxiolytic action, as well the use of long half-life medications. The predominance of Bromazepam use was paralleled by another Brazilian study, 13 but is not consistent with that observed in developed countries.…”
contrasting
confidence: 75%
“…8 Compared with other Brazilian studies, the use of benzodiazepines among older adults was higher than that observed in the adult population of the city of Pelotas-RS 17 and similar to that verified among the elderly population of a social center in Rio de Janeiro. 13 Regarding prescription, it is important to highlight that only 3% of benzodiazepine users had seen a psychiatrist in the prior year, while 95% had seen another specialist in the same period, suggesting that most of the prescriptions had been prescribed by non-psychiatrist physicians. The predominance of prescriptions of benzodiazepine by other specialists had also been observed in a cohort of elderly Americans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na Tabela 1, estão sintetizadas as características sociodemográ cas da nossa amostra institucionalizada. (Huf, Lopes & Rozenfeld, 2000) ao passo que, em Cuba parece ser o diazepam (Ricardo & Gárciga, 2010). …”
Section: Resultsunclassified
“…Alguns trabalhos realizados em nosso meio abordam o uso de medicamentos por pacientes idosos, como Huf et al (2000) e Teixeira et al (2000), entretanto, não exp1icitam o papel do farmacêutico na condução do regime terapêu-tico desse grupo de indivíduos.…”
unclassified